Effects of the Essential Oil from Pistacia lentiscus Var. chia on the Lateral Line System and the Gene Expression Profile of Zebrafish (Danio rerio) - Serifi, Iliana (Molecules, 2019)
Mastic essential oil exhibits anti-bacterial, anti-inflammatory, and anti-oxidant properties. With the growing interest of the use of mastic oil in the food and pharmaceutical industry, systematic in vivo studies are needed to address controlled usage and safety issues. In the present work we evaluated the safety of mastic oil using as a model the zebrafish lateral line system. In addition, we studied the gene expression profile of zebrafish fed with mastic oil-supplemented diet using microarray analysis. Our results showed that the hair cells of lateral line neuromasts are functional upon exposure of zebrafish larvae up to 20 ppm of mastic essential oil, while treatment with higher concentrations, 100 and 200 ppm, resulted in increased larvae mortality. Dietary supplementation of zebrafish with mastic essential oil led to differential expression of interferon response-related genes as well as the immune responsive gene 1 (irg1) that links cellular metabolism with immune defense. Notably, mucin 5.2, a constituent of the mucus hydrogel that protects the host against invading pathogens, was up-regulated. Our in vivo work provides information concerning the safety of mastic essential oil use and suggests dietary effects on gene expression related with the physical and immunochemical properties of the gastrointestinal system.